The Role of the West Java Regional Government in the Pandemic Period in Overcoming the Covid-19 Virus (Studies Analysis of Discourse on Decision Making by the Government of West Java Province) - Rayya Bethy; Prahastiwi Utari; Pawito (PT FORMOSA CENDEKIA GLOBAL, 2023)
At the beginning of the emergence of the Covid-19 outbreak, many things changed and were affected. Various kinds of fields and aspects in life also inevitably follow suit. Such as the economy, health, education, and so forth. It's no different in the field of government in Indonesia, there have been many changes and adjustments in order to cope with the effects of Covid-19. All regions in Indonesia apply the rules in accordance with the direction of the central government which then continues with the policies for each province. The Regional Government of West Java Province is considered quite attractive because it is responsive and effective in preventing the spread. Covid-19 cases in the area. The decision-making factor is one of the factors that is in the spotlight, in relation to internal communication.